The predictive value of signal peptide-CUB-EGF domain-containing protein1 (SCUBE1) in terms of the duration of peripheral ischemia and exposure to reperfusion - SÖĞÜT, Ozgur; Sonmez, ERTAN; SÖNMEZ, ERTAN; YIGIT, Mehmet; Turkdogan, Kenan Ahmet; KUCUKDAGLI, Okkes Taha; YİĞİT, Eda; Ozer, Omer Faruk; ÖZER, ÖMER FARUK; CİVELEK, Cemil (My University, 2017)
Biomarkers play important roles in the diagnosis and follow-up of ischemic diseases. This study investigated the predictive value of signal peptide-CUB-EGF domain-containing protein1 (SCUBE1) in rats with peripheral ischemia that were subjected to reperfusion. Forty rats were divided into five equal groups as follows (eight rats per group): a control group (to determine the basal levels of the markers), three ischemia groups (groups 1-3), and a reperfusion group (group 4). There were no significant differences in SCUBE1 levels between the control and ischemia groups. However, the SCUBE1 level was markedly higher in the reperfusion group than in the control and ischemia groups (p<0.05). The results indicate that SCUBE1 levels are not biomarkers of the induction of ischemia. However, they are potentially markers of reperfusion in rats with acute peripheral occlusions.